Empowerment of pregnant women and mothers of toddlers in increasing stunting knowledge - Muhamad Abi Zakaria; Dia Amalindah; Asroful Hulam Zamroni; Dilma’aarij Agustia (Universitas Muhammadiyah Magelang, 2023)
Stunting is a health problem that threatens the quality of human resources. The incidence of stunting in Indonesia is still above the target set by the World Health Organization. This is reflected in the creation of a policy to accelerate stunting reduction through Presidential Decree number 72 of 2021. Gunungkidul is the district with the highest number of stunting incidents in the Special Region of Yogyakarta Province. One of the factors that influences the incidence of stunting is the mother's knowledge about stunting. The aim of this service is to increase mothers' knowledge regarding stunting as an effort to prevent stunting incidents. The method used in this service is the lecture method using modules and discussion media. The results of this activity were attended by 26 pregnant women and mothers with children aged 0-5 years. As a result of this activity, participants experienced an increase in knowledge of 28.07. It is hoped that this increase in knowledge will enhance maternal participation in providing nutrition for babies to prevent stunting.